Cross-linked cyclodextrin-based material for treatment of metals and organic substances present in industrial discharge waters - Euvrard, Élise; Morin-Crini, Nadia; Druart, Coline; Bugnet, Justine; Martel, Bernard; Cosentino, Cesare; Moutarlier, Virginie; Crini, Grégorio (Beilstein Journal of Organic Chemistry, 2016)
In this study, a polymer, prepared by crosslinking cyclodextrin (CD) by means of a polycarboxylic acid, was used for the removal of pollutants from spiked solutions and discharge waters from the surface treatment industry. In spiked solutions containing five metals, sixteen polycyclic aromatic hydrocarbons (PAH) and three alkylphenols (AP), the material exhibited high adsorption capacities: >99% of Co2+, Ni2+ and Zn2+ were removed, between 65 and 82% of the PAHs, as well as 69 to 90% of the APs. Due to the structure of the polymer and its specific characteristics, such as the presence of carboxylic groups and CD cavities, the adsorption mechanism involves four main interactions: ion exchange, electrostatic interactions and precipitation for metal removal, and inclusion complexes for organics removal. In industrial discharge waters, competition effects appeared, especially because of the presence of calcium at high concentrations, which competed with other pollutants for the adsorption sites of the adsorbent.
Keywords: alkylphenols; adsorption; cyclodextrin; metals; polycyclic aromatic hydrocarbons